Technology Forecast for the Federal Judiciary. (Federal Probation, 2001)
This article was originally produced as a report by the Office of Information Technology for the Administrative Office of the U.S. Courts. A complement to the Long Range Plan for Information Technology in the Federal Judiciary, it reviews major trends that represent opportunities for the judiciary to invest in and exploit technology to improve business processes. Reprinted by permission of the publisher.